2020
DOI: 10.1186/s12872-020-01671-2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 inhibitor sildenafil in patients with heart failure with preserved ejection fraction and combined pre- and postcapillary pulmonary hypertension: a randomized open-label pilot study

Abstract: Background Heart failure with preserved ejection fraction (HFpEF) is frequently complicated by pulmonary hypertension (PH). A pulmonary vascular contribution could be considered as a substantial therapeutic target in HFpEF and PH and combined pre- and postcapillary PH (Cpc-PH). Methods We enrolled 50 patients with HFpEF and Cpc-PH who were determined by echocardiography to have pulmonary artery systolic pressure (PASP) > 40 mmHg, pulmonary vascular resistance > 3 Wood units, and/or transpulmonary gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
(68 reference statements)
1
24
0
5
Order By: Relevance
“…However, despite these reasonable concerns, several recent pharmaceutical and interventional trials targeting the pulmonary vasculature have shown benefit in CPCPH. [22][23][24][25] Whether targeted PH therapies may similarly benefit appropriately phenotyped patients with CA with CPCPH is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these reasonable concerns, several recent pharmaceutical and interventional trials targeting the pulmonary vasculature have shown benefit in CPCPH. [22][23][24][25] Whether targeted PH therapies may similarly benefit appropriately phenotyped patients with CA with CPCPH is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, Belyavskiy et al . 8 showed improvement in exercise capacity, pulmonary hemodynamics, and RV function in patients with HFpEF and combined pre- and post-capillary PH who were treated with sildenafil in a randomized open-label pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…8 Indeed, recently Guazzi’s positive results were corroborated in an independent sample of HFpEF patients with pulmonary hypertension. 17 Furthermore, in the RELAX trial the effects on exercise capacity were hampered by an abnormally high proportion of patients with chronotropic incompetence and an inferior dose and duration of therapy. More recently, the potential role of mitochondrial dysfunction and endoplasmic reticulum stress caused by sildenafil 18 and pharmacogenomics of liver metabolizing enzymes 19 were pointed out as other possible explanations.…”
Section: Discussionmentioning
confidence: 99%